2016
DOI: 10.1007/s12311-016-0826-5
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Pathology in Early Onset and Late Onset Essential Tremor

Abstract: Early onset and late onset essential tremor (ET) cases differ in several respects. Whether they differ with respect to cerebellar pathologic changes remains to be determined. We quantified a broad range of postmortem features (Purkinje cell (PC) counts, PC axonal torpedoes and associated axonal changes, heterotopic PCs, and hairy basket ratings) in 30 ET cases with age of tremor onset <50 years, 30 ET cases with age of tremor onset ≥50 years, and 30 controls (total n = 90). We also used two alternative age of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 48 publications
1
43
1
2
Order By: Relevance
“…The mean age of onset for ET is most commonly reported to be between 45 and 55 years, with a bimodal distribution [2123]. Of the ET cases in the ETCBR, there were 133 cases with clear documentation of age of tremor onset.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean age of onset for ET is most commonly reported to be between 45 and 55 years, with a bimodal distribution [2123]. Of the ET cases in the ETCBR, there were 133 cases with clear documentation of age of tremor onset.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we chose the age of onset of 50 to divide the early vs. late onset ET cases. Using data from our previous publications on the PC pathology in subgroups of ET cases and controls [21,24,25], we determined that with each ET group and control group composed of 30 subjects, we would be powered at 90% to detect differences of the magnitude previously detected [21,24,25]. Accordingly, we randomly selected 30 early onset ET cases, 30 late onset ET cases, and 30 controls in the current study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even the authors who suggested this term have defined "late-onset" differently in various papers (e.g., defining it as ≥46 years in another paper) [69]. Finally, postmortem studies of humans suggest that the same degenerative pathology is found in both younger onset and older onset ET cases to the same extent [70]. In summary, there is little current evidence to support the notion that age of onset is the basis for distinct and separable subtypes of ET or that cases whose disease begins after a certain age cutoff do not have ET [68].…”
Section: Additional Biological Considerations: Aging and Etmentioning
confidence: 99%
“…ET brains were from the Essential Tremor Centralized Brain Repository (ETCBR), a joint effort between investigators at Yale and Columbia Universities [33; 34]. ET diagnoses were all carefully assigned using three sequential methods, as described at length [14].…”
Section: Methodsmentioning
confidence: 99%